Polymorphisms and Haplotypes of the Estrogen Receptor-β Gene (ESR2) and Cardiovascular Disease in Men and Women - Rexrode, Kathryn M; Ridker, Paul M; Hegener, Hillary H; Buring, Julie E; Manson, JoAnn E; Zee, Robert YL (Clinical chemistry (Baltimore, Md.), 2007)
Background: Cohort studies suggest an association between variation in the estrogen receptor-α gene (ESR1) and cardiovascular disease (CVD), but data are lacking for the effect of variation in the estrogen receptor-β gene (ESR2). Methods: Three polymorphisms of the ESR2 gene, and their associated haplotypes, were evaluated in 296 white women from the Women’s Health Study and 566 white men from the Physicians’ Health Study who developed CVD [myocardial infarction (MI) or ischemic stroke], each matched 1:1 to a member of the cohort study who remained free from CVD. Blood samples and cardiovascular risk information were collected at baseline. Results: Women, but not men, who developed CVD or MI, but not ischemic stroke, were more likely to have the rs1271572 polymorphism variant T allele (P = 0.05 and 0.02) and less likely to have the rs1256049 polymorphism variant A allele (P = 0.003 and 0.004). No associations were observed for rs4986938. In conditional logistic multivariate regression, the rs1271572 variant was associated with increased odds of CVD [odds ratio (OR) = 1.49, 95% CI: 1.10–2.01] and MI (OR = 1.46, 95% CI: 0.96–2.23), whereas the rs1256049 variant was associated with decreased odds of CVD (OR = 0.37, 95% CI: 0.17–0.79) and MI (OR = 0.25, 95% CI: 0.09–0.73) in women. A common haplotype that included the rs1271572 variant was associated with a 7-fold increased risk of MI in women. Conclusions: Two tightly linked polymorphisms of ESR2 were associated with risk of CVD, particularly MI, in women but not men. Additional studies of ESR2 genetic variation and risk of CVD are warranted.